2008
DOI: 10.2147/ndt.s2627
|View full text |Cite
|
Sign up to set email alerts
|

Attention-deficit-hyperactivity disorder and reward deficiency syndrome

Abstract: Molecular genetic studies have identified several genes that may mediate susceptibility to attention defi cit hyperactivity disorder (ADHD). A consensus of the literature suggests that when there is a dysfunction in the "brain reward cascade," especially in the dopamine system, causing a low or hypo-dopaminergic trait, the brain may require dopamine for individuals to avoid unpleasant feelings. This high-risk genetic trait leads to multiple drugseeking behaviors, because the drugs activate release of dopamine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 101 publications
(103 reference statements)
0
48
0
Order By: Relevance
“…It had been suggested that the dopaminergic genes, especially the dopamine receptor D4 (DRD4), have been associated independently with both binge eating and ADHD 43 . Reward Deficiency Syndrome caused by abnormalities of dopaminergic genes could be a transdiagnostic feature between ADHD, eating disorder, and obesity 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…It had been suggested that the dopaminergic genes, especially the dopamine receptor D4 (DRD4), have been associated independently with both binge eating and ADHD 43 . Reward Deficiency Syndrome caused by abnormalities of dopaminergic genes could be a transdiagnostic feature between ADHD, eating disorder, and obesity 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…It seems unlikely that the core basic mechanisms underlying attentional deficits are the same in ADHD and schizophrenia. Although the dopamine system seems to be central in both disorders, ADHD is thought to be caused by an hypo-dopaminergic system[ 46 ] while schizophrenia is considered related to both a subcortical hyper-dopaminergic system (hyper-stimulation of D2 receptors in subcortical regions) and a prefrontal hypo-dopaminergic system (deficit in dopamine transmission at D1 receptors in the prefrontal cortex)[ 47 ]. However, despite their seemingly different origin, the general results of these attentional deficits are similar: they interfere with normal input processing, leading to similar specific impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Functional imaging studies have shown a decrease in basal ganglia (BG) and ventral striatum (VS) responses during reward anticipation [ 141 , 180 ], but a greater response in these areas during delivery of the reward [ 181 ]. Within the spectrum of psychopathology, control individuals with impulsive traits [ 182 ], as well as individuals with psychiatric diagnoses predisposing them to impulsive actions, such as ADHD, have shown heightened reward sensitivity and VS response to incentives [ 183 , 184 ]. Studies have aimed to understand the effects of adversity on individuals with particular gene variations.…”
Section: Environmental Input and Effects Of Psychotherapymentioning
confidence: 99%